From the Tide of the Hands - Dombrowsky, Yana (Auckland University of Techonology, 2022)
From the tide of the hands operates at a handheld and memorial scale, exploring the affection between hands, materials, and the imaginative space felt through gift-giving. Through a poetic phenomenology, I query rêverie as an oneiric, creative force that intimately negotiates the material entanglements of my practice. I consider ceramic artefacts and materials of practice as collaborators as I seek to open up ontological boundaries around what might constitute a hand *a point attached to a human/nonhuman body which holds, senses, directs, seizes, protects, possesses. In the process of sculpting, I listen to the materials and in our tactile union they take form. I carry these artefacts with me through my days, dispersing them as gifts when a moment of affection occurs. The result is a sprawling archaeology not for archive but dispersal and erosion. Affection propels the flow and fabrication of this research. I conceptualise affection as an emotive relation between things which summons a feeling leading to action: as in affect. It occurs in the softened spaces of daily encounters, conversations, and daydreams that ooze between my textual and sculptural material research. Acting as tokens of affection, the artefacts sculpted by my hands create a space of memory that are then dispersed across the hands of the human and more-than-human beings proximate to me.*Cradled by the hand of a dear friend, held up to the sky by the Prunus Campanulata in my mother’s garden, slipped into the pocket of an unknown’s jacket, sealed by a skin of crystallised salt in my studio. When held as prosaic charms indexing affection, memory and feeling, the artefacts take on an aura which set in motion an entangled web of relations within the everyday. Here, I define aura as an energetic force, whereby the artefacts possess a liveliness and are able to hold their own affectionate gaze. Through this understanding of aura, the artefacts assert a kind of autonomy, as in the power to affect the receiver. By holding and being held by the artefacts, a feeling is felt; an oneiric image is summoned. By dispersing artefacts of practice as gifts, I nurture relationships beyond linguistic rapports, generating a reciprocal cycle of feeling. Furthermore, these everyday dispersals seek an alternative system of value to one of commodification and monetary exchange. I avoid articulating any intended use of these artefacts; their being in the world is one that I leave open to not only those I gift them to but to the artefacts themselves.